2014
DOI: 10.1186/1750-1172-9-92
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine transporter-2 deficiency: outcome and treatment monitoring

Abstract: BackgroundThe clinical characteristics distinguishing treatable thiamine transporter-2 deficiency (ThTR2) due to SLC19A3 genetic defects from the other devastating causes of Leigh syndrome are sparse.MethodsWe report the clinical follow-up after thiamine and biotin supplementation in four children with ThTR2 deficiency presenting with Leigh and biotin-thiamine-responsive basal ganglia disease phenotypes. We established whole-blood thiamine reference values in 106 non-neurological affected children and monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
(62 reference statements)
2
41
0
Order By: Relevance
“…Recently, Ortigoza-Escobar et al showed that treatment monitoring relied on whole blood thiamine diphosphate concentrations. 11 Overall, our findings would suggest that the combination of biotin plus thiamine is not superior to thiamine alone in the treatment of biotin-responsive basal ganglia disease. However, two limitations should be considered in the interpretations of our data: this study reports the short-term follow-up data of a single center open-label study; in our experience patients with BBGD may remain asymptomatic without treatment during several years, and second: the small number of patients included.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, Ortigoza-Escobar et al showed that treatment monitoring relied on whole blood thiamine diphosphate concentrations. 11 Overall, our findings would suggest that the combination of biotin plus thiamine is not superior to thiamine alone in the treatment of biotin-responsive basal ganglia disease. However, two limitations should be considered in the interpretations of our data: this study reports the short-term follow-up data of a single center open-label study; in our experience patients with BBGD may remain asymptomatic without treatment during several years, and second: the small number of patients included.…”
Section: Discussionmentioning
confidence: 76%
“…70 Unlike typical LS, patients with BTBGD can show significant clinical and neuroradiological improvement following administration of thiamine and high-dose biotin, particularly when commenced early in the disease course. 71 Patients with SLC19A3 mutations have been described as having "treatable" or "reversible" LS.…”
Section: Pyruvate Dehydrogenase Complex Deficiencymentioning
confidence: 99%
“…Genetic disorders of thiamine metabolism that lead to neurological diseases can be treated with highdose thiamine [11,12,13]. Recently, good results in sporadic degenerative diseases have been achieved with the same treatment [9].…”
Section: Discussionmentioning
confidence: 99%